Carbon nanotube buckypaper and buckypaper/polypropylene composites for high shielding effectiveness and absorption-dominated shielding material. (8th September 2019) - Hu, Yunping; Li, Dongcheng; Wu, Lu; Yang, Junyu; Jian, Xigao; Bin, Yuezhen
Abstract: Buckypaper (BP) was prepared as efficient electromagnetic interference (EMI) shielding materials in X-band (8.2–12.4 GHz). The EMI shielding effectiveness (SE) of 31.2 dB and a high specific SE of 19850 dB cm 2 /g have been realized by BP of 35 μm thick. Notably, the absorption-dominated SE above 100 dB can be achieved by constructing multilayer structure or sandwich structure using BP and polypropylene sheet. For multilayer structure, the increment in EMI SE is contributed by absorption loss and reveals a slow decline trend on the whole with BP layers increasing. For sandwich structure, the improvement in SE is ascribed to the constructive interference, and there is a best polypropylene sheet thickness (0.32–0.48λ, λ = 25 mm) to realize the maximization of SE. In comparison with multilayer structure of the same components of BPs, the SE of sandwich structure with one and two wave-transmitting layers significantly increased by 61.5% and 90% respectively.